Tendências de dilemas nas políticas públicas de formação de professores para as séries iniciais: o caso do Pará - Arlete Maria Monte de Camargo (2004)
The main objective of this study was to analyse the curricular changing processes of teacher education programs that aim at educating teachers for the first grades of fundamental school that have taken place at three universities in the state of Pará, northern region of Brazil. The universities are Universidade Estadual do Pará (UEPA), Universidade Federal do Pará (UFPA), and Universidade da Amazônia (UNAMA). In order to accomplish this objective I analysed different texts on the issue from different sources, which include official texts, academic texts, and non-official and non-academic texts by representatives of groups involved in curricular discussions. I also analysed the new curricula for teacher education programs aiming at educating teachers for the first grades of fundamental school at the previously mentioned universities. I was particularly interested in understanding how the different conceptions present in those texts influenced the new teacher education programs. Two main contributions from the official texts were identified: the curricular constituents of teaching practice, and the decisions about what the table of contents for the fundamental school should be. One contribution from the texts generated inside the Associação Nacional para a Formação de Profissionais da Educação (ANFOPE) was identified: the embodiment of concepts such as national basic curriculum and pedagogical work, specially within Pedagogy Programs that aim at educating teachers for the first grades of fundamental school. I believe it is worthy mentioning that the different conceptions of the groups that had discussed curricular changing inside the different universities is an embodiment of their beliefs and that they have been of primary importance to the processes. The analysis of the different curricula makes it evident that they display an interplay of different voices from different texts.